2013
DOI: 10.1016/j.matdes.2013.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Flexural properties, thermal conductivity and electrical resistivity of prealloyed and master alloy addition powder metallurgy Ti–6Al–4V

Abstract: A comparison between the properties achievable by processing the Ti-6Al-4V alloys by means of two powder metallurgy approaches, precisely prealloyed and master alloy addition, was carried out. Prealloyed and master alloy addition hydride-dehydirde powders characterised by an irregular morphology were shaped by means of cold uniaxial pressing and high vacuum sintered considering the effect of the variation of the sintering temperature and of the dwell time. Generally, the higher the temperature and the longer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…The variation of the mechanical properties reported in this work with the sintering temperature are consistent with the results found when assessing the sinterability of the Ti-6Al-4V-BE and Ti-6Al-4V-PA alloys over a wider range of processing temperatures (i.e. 900-1400ºC) [18,19] or the influence of the sintering time [26].…”
Section: Accepted M Manuscriptsupporting
confidence: 88%
“…The variation of the mechanical properties reported in this work with the sintering temperature are consistent with the results found when assessing the sinterability of the Ti-6Al-4V-BE and Ti-6Al-4V-PA alloys over a wider range of processing temperatures (i.e. 900-1400ºC) [18,19] or the influence of the sintering time [26].…”
Section: Accepted M Manuscriptsupporting
confidence: 88%
“…The value of the corresponding relative density (i.e. 94-96%) are common values for titanium alloys obtained by pressing and sintering (Abkowitz and Rowell, 1986;Bolzoni et al, 2013;Ivasishin, 2005). Table 2 shows the results of the chemical analysis carried out on sintered Ti-6Al-7Nb…”
Section: Characterisation Of the Sintered Ti-6al-7nb Componentsmentioning
confidence: 99%
“…The sintering temperature range considered was between 1250 1C and 1350 1C whilst the sintering time was kept constant at 120 min. These parameters were selected on the base of a previous study where it was demonstrated that the increment of the sintering time is not as effective as the increment of the processing temperature to reach high relative density values [17]. It is worth mentioning that due to the layout of the furnace, sintering was carried out discontinuously (by-batches) but a minimum of three samples per material/condition were considered each time.…”
Section: Shaping and Sintering Of The Ti-3al-25v Powdersmentioning
confidence: 99%